Characterization of CD4+ T cells primed and boosted by MHCII primary uveal melanoma cell-based vaccines - Kittler, Julia; Sommer, Jonas; Fischer, Anika; Britting, Sabine; Karg, Margarete; Bock, Barbara; Atreya, Imke; Heindl, Ludwig M.; Mackensen, Andreas; Bosch, Jacobus J. (Oncotarget, 2019)
Uveal melanoma is the most common primary malignancy of the eye in adults. Despite significant improvements in treatment of the primary tumor, to date none of these therapies prevent metastatic disease or improve overall survival. We are exploring immunotherapeutic options for metastatic uveal melanoma using MHC II uveal melanoma cell-based vaccines that target the activation of tumor-reactive CD4+ T cells. Previously, we showed that these uveal melanoma cell-based vaccines activate CD4+ T cells within total peripheral blood lymphocytes (PBMC). Since PBMC include professional antigen presenting cells, we now demonstrate that Mel202/ DR1/CD80 vaccine cells directly activate a diverse repertoire of purified, naïve CD4+ T cells. The activated CD4+ T cells proliferated, secreted high amounts of interferon gamma (IFNγ) and produced a heterogeneous profile of Th1, Th2 and Th17 cytokines. Analysis of the TCR-Vβ-repertoire showed that a polyclonal T cell response was induced, suggesting the capacity of vaccine-activated CD4+ T cells to target multiple tumor (neo)antigens. In addition, a subset of the responding CD4+ T cells expressed forkhead box protein P3 (FoxP3), indicating that although a regulatory component of the vaccine-activated CD4+ T cell response was induced, the anti-tumor vaccine response was not limited by these regulatory CD4+ T cells. Finally, Mel202/DR1/CD80 uveal melanoma vaccine cells expressed the intercellular adhesion molecule 1 (ICAM-1) that was pivotal for CD4+ T cell activation via lymphocyte function-associated antigen 1(LFA-1). In conclusion, MHC II uveal melanoma vaccines activate purified CD4+ T cells and may serve as a novel immunotherapy for uveal melanoma patients.
CRIS-Team Scopus Importer:2019-06-07
Keywords: CD4+ T cells; ICAM-1; T cell activation; Tumor immunity; Uveal melanoma

Drei Generationen Leiden: Cryopyrin-assoziiertes periodisches Syndrom mit familiärer NLRP3-Mutation - Wagner, Nicola; Manger, Bernhard; Kittler, Julia; Rech, Jürgen; Sticherling, Michael; Berking, Carola; Kirchberger, Michael (Journal der Deutschen Dermatologischen Gesellschaft, 2022)
CRIS-Team Scopus Importer:2022-02-04

German Mobile Apps in Rheumatology: Review and Analysis Using the Mobile Application Rating Scale (MARS) - Knitza, Johannes; Tascilar, Koray; Messner, Eva-Maria; Meyer, Marco; Vossen, Diana; Pulla, Almut; Bosch, Philipp; Kittler, Julia; Kleyer, Arnd; Sewerin, Philipp; Mucke, Johanna; Haase, Isabell; et al. (JMIR mHealth and uHealth, 2019)
Background: Chronic rheumatic diseases need long-term treatment and professional supervision. Mobile apps promise to improve the lives of patients and physicians. In routine practice, however, rheumatology apps are largely unknown and little is known about their quality and safety.
CRIS-Team WoS Importer:2019-08-27

Mobile Apps in Rheumatology: Review and Analysis Using the Mobile App Rating Scale (MARS) - Knitza, Johannes; Tascilar, Koray; Messner, Eva-Maria; Meyer, Marco; Vossen, Diana; Pulla, Almut; Bosch, Philipp; Kittler, Julia; Kleyer, Arnd; Sewerin, Philipp; Mucke, Johanna; Haase, Isabell; et al. (ARTHRITIS & RHEUMATOLOGY, 2019)
CRIS-Team WoS Importer:2020-02-07

THE IMPACT OF IL-17A THERAPY ON IGG SIALYLATION IN HUMANS - Pfeifle, René; Kittler, Julia; Wuhrer, M.; Schett, Georg; Krönke, Gerhard (ANNALS OF THE RHEUMATIC DISEASES, 2021)
CRIS-Team WoS Importer:2021-09-24

THE ROLE OF THE IL-23/TH17 AXIS AS MODULATOR OF B CELL-MEDIATED (AUTO)IMMUNE RESPONSES - Pfeifle, René; Kittler, Julia; Rothe, Tobias; Schett, Georg; Krönke, Gerhard (2019)
EVALuna2:213239

Three generations of suffering: cryopyrin-associated periodic syndrome with NLRP3 mutation in a family - Wagner, Nicola; Manger, Bernhard; Kittler, Julia; Rech, Jürgen; Sticherling, Michael; Berking, Carola; Kirchberger, Michael Constantin (Journal der Deutschen Dermatologischen Gesellschaft, 2021)
CRIS-Team Scopus Importer:2021-12-24